The effectiveness of telemedicine in the management of chronic heart disease – a systematic review - Kruse, Clemens S (JRSM Open, 2017)
OBJECTIVE: The primary objective of this systematic review is to assess the effectiveness of telemedicine in managing chronic heart disease patients concerning improvement in varied health attributes. DESIGN: This review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard. SETTING: We adopted a logical search process used in two main research databases, the Cumulative Index to Nursing and Allied Health Literature and PubMed (MEDLINE). Four reviewers meticulously screened 151 abstracts to determine relevancy and significance to our research objectives. The final sample in the literature review consisted of 20 articles. MAIN OUTCOME MEASURES: We looked for improved medical outcomes as the main outcome measure. RESULTS: Our results indicated that telemedicine is highly associated with the reduction in hospitalisations and readmissions (9 of 20 articles, 45%). The other significant attributes most commonly encountered were improved mortality and cost-effectiveness (both 40%) and improved health outcomes (35%). Patient satisfaction occurred the least in the literature, mentioned in only 2 of 20 articles (10%). There was no significant mention of an increase in patient satisfaction because of telemedicine. CONCLUSIONS: We concluded that telemedicine is considered to be effective in quality measures such as readmissions, moderately effective in health outcomes, only marginally effective in customer satisfaction. Telemedicine shows promise on an alternative modality of care for cardiovascular disease, but additional exploration should continue to quantify the quality measures.